DIGITALIZATION IN DENTISTRY: USING CRM AND MEDICAL INFORMATION SYSTEMS IN DENTAL CLINIC MANAGEMENT AND DEVELOPMENT (International journal of medical sciences, 2026)
The digital transformation of healthcare defines modern trends in the development of dentistry as a high-tech and socially significant branch of medicine. This article presents a comprehensive analysis of the digitalization of a dental clinic, focusing on the implementation of CRM and medical information systems. The functional capabilities and management potential of amoCRM, Bifoza, and OneMed systems are examined. The clinical, organizational, economic, and social effects of implementing digital solutions, as well as issues of information security, legal regulation, and personnel training, are analyzed. It is substantiated that digitalization creates a patient-oriented model of dental care, improves the quality of treatment, and enhances the sustainability of a medical organization.